Dynamic Connectedness and Investment Strategies between Commodities and ESG Stocks: Evidence from India - Ishwar Sharma; Meera Bamba; Bhawana Verma; Bharti Verma (Australasian Accounting, Business and Finance Journal, 2024)
The study investigates the connectedness between commodities and ESG stocks of India using the extended joint connectedness approach. The study found a time-varying relationship between commodities and ESG stocks. It also discovered that there is a low spillover between the two. However, the total connectedness increased during the Russia-Ukraine war but remained low. The study found that crude oil and natural gas act as net transmitters, while ESG stocks and gold act as net receivers. ESG stocks are negatively connected with gold and have a low degree of positive correlation with crude oil and natural gas. Therefore, portfolio diversification opportunities exist between commodities and ESG stocks. The study exhibits that investors may derive significant benefits by adjusting their portfolios based on the optimum weights provided by the portfolio construction technique. The study provides valuable insights for portfolio managers, investors, and policymakers.
Keywords: ESG; Commodities; connectedness approach; Portfolio diversification; SDG 8; SDG Target 8.1